2018
DOI: 10.1111/bph.14134
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐independent activation of acid‐sensing ion channel 3 by an alkaloid, lindoldhamine, from Laurus nobilis

Abstract: We describe a novel ASIC subtype-specific agonist LIN, which induced proton-independent activation of human and rat ASIC3 channels at physiological pH. LIN also acts as a positive allosteric modulator of human, but not rat, ASIC3 channels. This unique, species-selective, ligand of ASIC3, opens new avenues in studies of ASIC structure and function, as well as providing new approaches to drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Xenopus laevis frogs () were purchased from the Koltzov Institute of Developmental Biology, RAS. Oocytes were prepared as described previously (Osmakov et al, 2018). In brief, frogs were cooled down to 2–4°C to provide anesthesia and ~200 oocytes were surgically removed from the ovarian tissue of the animals through a small incision in the abdominal wall, which then was sewn with a single stitch.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xenopus laevis frogs () were purchased from the Koltzov Institute of Developmental Biology, RAS. Oocytes were prepared as described previously (Osmakov et al, 2018). In brief, frogs were cooled down to 2–4°C to provide anesthesia and ~200 oocytes were surgically removed from the ovarian tissue of the animals through a small incision in the abdominal wall, which then was sewn with a single stitch.…”
Section: Methodsmentioning
confidence: 99%
“…Two‐electrode voltage‐clamp recordings were performed using the GeneClamp500 amplifier (Axon Instruments) at the holding potential of −50 mV as described in (Osmakov et al, 2018). The data were filtered at 20 Hz and digitized at 100 Hz using the L780 AD converter (L‐Card).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also identified the endogenous isoquinoline alkaloids, the precursors of endogenous morphine biosynthesis, as the non-proton ligands of ASIC3 [ 90 ]. Moreover, alkaloid lindoldhamine isolated from Laurus nobilis is another non-proton ligand of ASIC3 opening the channel under neutral or even more alkaline (pH > 7.4) conditions [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…MitTx also modulates ASIC2a pH sensitivity. Recently, lindoldhamine, an alkaloid from Laurus nobilis , was shown to activate the ASIC3 in a proton-independent form and to act as a positive allosteric modulator of human and rat ASIC3 channels ( Osmakov et al, 2018 ).…”
Section: Asicsmentioning
confidence: 99%